2018
DOI: 10.1002/met.1722
|View full text |Cite
|
Sign up to set email alerts
|

Hazmat risk area assessment by atmospheric dispersion modelling using Latin hypercube sampling with weather ensemble

Abstract: Atmospheric dispersion modelling is always encumbered by errors and uncertainties originating from different aspects of the weather description as well as the source and dispersion models. Even so, the typical results from these kinds of studies are limited to one realization with no measure of uncertainties in either the temporal or spatial dimensions. This result is then to be interpreted as the most probable outcome given the current information. However, in many situations this limited result and the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A number of other studies have also considered hypothetical releases of radioactive material and considered how to increase the computational efficiency of running dispersion ensembles (e.g. Sørensen et al, 2020;Sigg et al, 2018). Korsakissok et al (2020) compared ensemble forecasts for two hypothetical accidents in Europe using a range of different dispersion models and ensemble meteorology from the HARMONIE meteorological model.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies have also considered hypothetical releases of radioactive material and considered how to increase the computational efficiency of running dispersion ensembles (e.g. Sørensen et al, 2020;Sigg et al, 2018). Korsakissok et al (2020) compared ensemble forecasts for two hypothetical accidents in Europe using a range of different dispersion models and ensemble meteorology from the HARMONIE meteorological model.…”
Section: Introductionmentioning
confidence: 99%
“…Galmarini et al (2010) demonstrated that a single dispersion model using an ensemble meteorological forecast could give comparable performance to a multi-model approach. The use of disper-sion ensembles has become increasingly common in recent years (Sigg et al, 2018;Zidikheri et al, 2018;Maurer et al, 2021) with enhancements to computing power making such approaches now viable for operational implementations.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques are available to understand uncertainties in atmospheric dispersion outputs, with ensemble-based approaches becoming increasingly common over recent years (Sigg et al, 2018;Zidikheri et al, 2018;Maurer et al, 2021). In weather forecasting, ensemble prediction systems first became operational in the early 1990s, with pioneering global ensemble forecasts issued by the European Centre for Medium-Range Weather Forecasts (ECMWF: Buizza and Palmer (1995); Buizza et al (2007)) and the National Centers for Environmental Prediction (NCEP: Toth and Kalnay (1993)).…”
mentioning
confidence: 99%